Research on the Impact of the Sand and Dust Ingestion Test on the Overall Performance of Turboshaft Engines - Qingping Wang; Wenchao Zhang; Xin Yuan; Yixuan Wang; Zhongliang Shen; Fei Wang (Aerospace)
Based on GJB 242A, a detailed experimental procedure for the sand and dust ingestion of a turboshaft engine was established. A specific type of turboshaft engine was used to conduct 54 h full-engine sand and dust ingestion experiments. This research studied the impact of sand and dust ingestion on the engine’s common operating line, power loss, specific fuel consumption, and gas turbine exhaust temperature, among other performance parameters. The experimental results indicate that under the same equivalent power conditions, the impact of short-term sand and dust ingestion on the engine’s common operating line is minimal; as the sand and dust ingestion time increases, the equivalent airflow decreases significantly, causing the engine’s common operating line to shift upward and the gas turbine exhaust temperature to rise, with the maximum increase reaching 27.9 °C. However, the impact of sand and dust ingestion on the gas turbine exhaust temperature at high power levels is relatively small. After completing the sand and dust ingestion test, the engine’s power loss at maximum continuous operation was approximately 11.33%, and the specific fuel consumption increased by about 6.05%. The power loss does not meet the requirement of being less than 10% as stipulated in GJB 242A. Based on the engine disassembly inspection results, subsequent improvement suggestions were proposed. The findings of this paper can provide a scientific and rational basis and reference for the sand and dust resistance design and sand ingestion testing of similar aero-engines.